LASAEO FOLKLORE SPEECH CODE OF THE PAMONA TRIBE - Putri Ayuningsi Ida; Ulinsa Ulinsa; Pratama Bayu Santosa (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Lasaeo Folklore Speech Code of the Pamona Tribe. This study aims to describe code switching and code mixing contained in the Lasaeo folklore. This type of qualitative research. Methods and Data Collection Techniques used There is a method of observing. The data analysis technique using the method is the extralingual equivalent method. The method used in the stage of presenting the results of data analysis in this study is an informal method. The results of this study are as follows. The results of the study are that the first symptom of code switching found in the Pamona Lasaeo folklore occurs in two formations, namely the Pamona language and the Indonesian language. The two code mixes found in the Lasaeo folklore are in the form of basic words, repeated words, phrases and clauses. The function of code switching and code mixing in the folklore of Pamona Lasaeo is to explain, command, ask questions, and confirm intentions. Mixing code in lasaeo folklore when interacting using Indonesian by deliberately mixing Pamona as an ethnic language so that there is intimacy between speakers and speech partners.